#TITLE_ALTERNATIVE# - NURRAHMAN (NIM 13204184), RISMAN
In this final project, an implementation of Multi Channel Active Noise Control based on Digital Signal Processing (DSP) TMSC6713 to attenuate noise in open space has been done. Sinusoidal signal, record of fan noise and fan noise are used in this experiment. This experiment based on Adjoint LMS algorithm which is a modification of FX-LMS algorithm.Experimental result show good attenuation on sinusoidal signal that reach 22 dB. Attenuation on record of fan noise reach 5 dB. Attenuation for fan noise is 2 dB.